Fine Tuning of Traumatic Brain Injury Management in Neurointensive Care—Indicative Observations and Future Perspectives - Svedung Wettervik, Teodor M.; Lewén, Anders; Enblad, Per (Frontiers in Neurology, 2021)
Neurointensive care (NIC) has contributed to great improvements in clinical outcome for patients with severe traumatic brain injury (TBI) by preventing, detecting, and treating secondary insults and thereby reducing secondary brain injury. Traditional NIC management has mainly focused on generally applicable escalated treatment protocols to avoid high intracranial pressure (ICP) and to keep the cerebral perfusion pressure (CPP) at sufficiently high levels. However, TBI is a very heterogeneous disease regarding type of injury, age, co-morbidity, secondary injury mechanisms, etc. In recent years, the introduction of multimodality monitoring, including e.g. pressure autoregulation, brain tissue oxygenation, and cerebral energy metabolism, in addition to ICP and CPP, has increased the understanding of the complex pathophysiology and the physiological effects of treatments in this condition. In this article, we will present some potential future approaches for more individualized patient management and fine tuning of NIC, taking advantage of multimodal monitoring to further improve outcome after severe TBI.